Preparation and in vitro-in vivo evaluation of acyclovir floating tablets - Rahim Bahri-Najafi; Abolfazl Mostafavi; Naser Tavakoli; Somayeh Taymouri; Mohammad-Mehdi Shahraki (Wolters Kluwer Medknow Publications, 2017)
In the current study, floating dosage form containing acyclovir was developed to increase its oral bioavailability. Effervescent floating tablets containing 200 mg acyclovir were prepared by direct compression method with three different rate controlling polymers including Hydroxypropyl methylcellulose K4M, Carbapol 934, and Polyvinylpyrrolidone. Optimized formulation showed good floating properties and in vitro drug release characteristics with mean dissolution time and dissolution efficacy of about 4.76 h and 54.33%, respectively. X-ray radiography exhibited that the tablet would reside in the stomach for about 5 ± 0.7 h. After oral administration of floating tablet containing 200 mg acyclovir, the Cmax, Tmax, and AUC0-∞ of optimized gastroretentive formulation were found to be 551 ± 141 ng/mL, 2.75 ± 0.25 h and 3761 ± 909.6 ng/mL/h, respectively.